THE ROLE OF BANKING SERVICES IN SHAPING THE DIGITAL ECONOMY - Urunbaeva Yulduz Pirnazarovna (Research Parks Publishers, 2023)
the article considers the role of banking services in the context of the development of digital economy and financial technologies. Ways to implement the digital economy based on blockchain technologies were also seen. Management processes of